Resolution of the method of direction finding, which based on j - correlation processing - Харченко, В.П.; Сорочан, А.Г. (Proceedings of National Aviation University (archive), 2010)
The analysis of the resolution of the J-correlation method of direction finding. The expressions defining the standard deviations of the difference of time delays of signals caused by the angular divergence between the directions of two equidistant targets.